Assessing durabilty in geopolymer composites with brick powder and recycled concrete aggregate - Aygun, Beyza Fahriye; Akturk, Birkan; Uysal, Mucteba; Boutkhil, Hanane (YILDIZ TECHNICAL UNIV, 2025)
This study examines the durability properties of fiber-reinforced geopolymer composites (GCs) incorporating recycled concrete aggregate (RCA) and brick powder (BP). The utilization of industrial by-products, including metakaolin (MK), fly ash (FA), red mud (RM), and slag (GBFS), in conjunction with alkaline activators, permitted the incorporation of three distinct fiber types-steel (SF), polyamide (PAF), and polyethylene (PEF)-at varying ratios (0.25%-1.00%). The resulting composites were subjected to thermal curing at 60 degrees C for 24 hours. The ensuing results demonstrated a notable enhancement in mechanical properties. Adding 1%, PEF resulted in a 25% increase in compressive strength, reaching 46.65 MPa, while incorporating 0.75% PEF led to a 35% enhancement in flexural strength, reaching 8.73 MPa, compared to the control samples. The durability tests indicated that after 180 freezethaw cycles, the strength loss for 0.25% SF was reduced to 6.97% compared to a 37.5% loss in controls. High-temperature resistance tests demonstrated that composites retained up to 89% of their compressive strength at 300 degrees C and about 50% at 600 degrees C. The 0.75% PEF series exhibited the most robust performance. Additionally, sulfate resistance was enhanced, with less than a 10% strength loss after nine months in 10% Mg2SO4 and Na2SO4 solutions. These findings indicate the potential of fiber-reinforced GCs as durable, high-performance materials for sustainable construction. They demonstrate the effective utilization of industrial by-products while maintaining structural integrity under challenging environmental conditions.
Keywords: Brick Powder; Geopolymer Composites; Recycling Concrete Aggregate; Mechanical and Durability Properties; Sustainability; SULFATE RESISTANCE; MORTAR; Engineering